Going 3D with technology: an overarching approach for language teachers - Hendryx, Jason D. (Colombian Applied Linguistics Journal, 2016)
Grounded in over a decade of language classroom observations, in multiple institutions of secondary and higher education in several countries, across over a dozen languages, three key features of what appear to be successful applications of technology by instructors in these classes for language teaching emerged. These features came to be identified as directional, developmental, and decisive—hereafter referred to as the 3Ds. Observational data suggests that when an instructor embraces any of the 3Ds while using technology for teaching and learning purposes, the more successful that application of technology seems to be. Success here should be understood as higher levels of student interaction, engagement, and motivation, with more kinds and types of student language being produced. Meanwhile, observations of instructors who did not utilize any of the 3Ds, revealed stiff, uninspiring uses of technology, oftentimes devoid of context, which did not result in much, if any, student interaction or language production.